Effects of flowering period and cultivation practices on volatile organic compounds in Sanqi flowers - Yang, Fan; Li, Yue; Yi, Tongning; Hei, Jingying; Wang, Biao; He, Xiahong; Wang, Shu (Frontiers in Plant Science, 2026)
Sanqi flower holds broad application prospects in the food industry due to its rich bioactive components and potential health benefits. However, limited information is available regarding the variation of volatile organic compounds (VOCs) in the Sanqi flowers within Sanqi–Pinus armandii (SPA) and Sanqi–Pinus yunnanensis (SPY) agroforestry systems. Here, the VOCs in Sanqi flowers were compared and analyzed using headspace–solid phase microextraction (HS-SPME) and gas chromatography–mass spectrometry (GC-MS). A total of 60 and 55 VOCs were identified in the Sanqi flowers obtained from the SPY and SPA agroforestry systems, respectively. Terpenes were found to be the predominant components. Moreover, Germacrene D (ranging from 21.35–26.24% to 15.46–24.41%), β-Ocimene (ranging from 21.28–6.60% to 1.21–22.48%) and β-Elemene (ranging from 11.72–13.52% to 9.15–18.77%) were the most abundant in the SPY and SPA systems. Hierarchical clustering analysis (HCA) showed that the VOCs in the Sanqi flowers within the SPY system were clustered into one group. Principal component analysis (PCA) indicated that the VOCs in Sanqi flowers were primarily influenced by the cultivation system. Furthermore, trans-Nerolidol, (E)-4,8-Dimethylnona-1,3,7-triene and γ-Muurolene from the PYS system and Cubenene, Espatulenol, and Bicyclogermacrene from the PAS system can serve as the distinctive VOCs in Sanqi flowers. Redundancy analysis (RDA) revealed that the main factors affecting the VOCs in Sanqi flowers were humidity, followed by temperature. This study provides a theoretical basis for understanding the impact of different agroforestry systems on the VOCs of Sanqi flowers and offers insights into optimizing cultivation practices to enhance the medicinal edible qualities of Sanqi.